Changing Positive Academic Emotions of Art Students Utilizing Computer Information Technology Based on the Perspective of Teaching - Yihong Sun (Applied Bionics and Biomechanics)
This study is aimed at exploring the influencing factors on the altering academic mood of art students. With the assistance of computer information technology, the survey utilizing a questionnaire is conducted to explore the influence of different coping styles on the academic moods of art students when the influence of demographic variables is under consideration. It is concluded that the condition of being the only child of art students has a positive and high arousal emotional score of 80.93, which is significantly higher than that of not being an only-child art student of 78.61. Art students are more inclined to take a positive coping style. The scores of negative and high arousal academic emotions are found to be 79.3, 80, and 96.83, respectively, when the grade changes from 1 through 3. The general trend is that the scores of negative and high arousal academic emotions increase when grades go up. Art students experience more negative academic emotions than positive academic emotions when the general characteristics of art students’ academic emotions are under consideration. Because females are more sensitive and delicate, they experience more negative academic emotions. Besides, while a positive coping style can positively predict art students’ positive academic mood, a negative coping style can positively estimate the negative academic mood. It is concluded that the outcomes could provide a reference for the prediction of academic mood changes in art students.